A Facile Review on the Sorption of Heavy Metals and Dyes Using Bionanocomposites. (7th March 2022) - Aigbe, Uyiosa Osagie; Ukhurebor, Kingsley Eghonghon; Onyancha, Robert Birundu; Okundaye, Benedict; Pal, Kaushik; Osibote, Otolorin Adelaja; Esiekpe, Ese Lawrence; Kusuma, Heri Septya; Darmokoesoemo, Handoko
Abstract : Presently, hazardous metal and dye removal from wastewater is one of the major areas of research focus. For the elimination of these contaminants, many approaches have been devised and applied. However, the accomplishment of various water treatment processes has largely depended on the medium utilized and the associated problem with the leaching of harmful compounds into the water process with most commercial and chemically manufactured materials for water treatment processes. Hence, this study is aimed at reviewing existing studies on the sorption of heavy metals (HMs) and dyes using bionanocomposites (BNCs). The key focus of this review is on the development of eco-friendly, effective, and appropriate nanoadsorbents that could accomplish superior and enhanced contaminant sequestration using BNCs owing to their biodegradability, biocompatible, environmentally friendly, and not posing as secondary waste to the environment. The sorption of most pollutants was observed to be pH, sorbent dosage, and initial contaminant concentration-dependent, with most contaminants' elimination taking place in the pH range of 2-10. The sorption process of HMs and dyes to various BNCs was superlatively depicted utilizing the Langmuir (LNR) and Freundlich (FL) as well as the pseudo-second-order (PSO) models, suggestive of the sorption process of a monolayer and multilayer and the chemisorption process, the rate-limiting stage in surface sorption. The established sorption capacities for the reviewed sorption process for various contaminants ranged from 1.47 to 740.97 mg/g. Future prospective for the treatment and remediation of contaminated water using BNCs was also discussed.